Portable X-ray fluorescence of zinc and selenium with nail clippings – visit 3 of the Mother and Infant Nutrition Investigation (MINI) - David E.B. Fleming; Andrianna R. Scott; Jasmine A. Ouellette; Jong Sung Kim; Abir Lefsay; Ying Jin; Jane Coad; Louise Brough (Journal of Trace Elements in Medicine and Biology, 2025)

Green-lipped (greenshell™) mussel (Perna canaliculus) extract supplementation in treatment of osteoarthritis: a systematic review - Maryam Abshirini; Jane Coad; Frances M. Wolber; Pamela von Hurst; Matthew R. Miller; Hong Sabrina Tian; Marlena C. Kruger (Inflammopharmacology, 2021)
Objectives Intervention studies using New Zealand green-lipped or greenshell™ mussel (GSM) ( Perna canaliculus ) extract in osteoarthritis (OA) patients have shown effective pain relief. This systematic review summarises the efficacy of GSM extracts in the treatment of OA. Methods A literature search of the three databases EMBASE, MEDLINE, and Scopus was performed to identify relevant articles published up to March 2020. Inclusion criteria were clinical trials published in English measuring the effect of supplementation of whole or a lipid extract from GSM on pain and mobility outcomes in OA patients. Results A total of nine clinical trials were included in systematic review, from which five studies were considered appropriate for inclusion in a forest plot. Pooled results showed that GSM extracts (lipid extract or whole powder) provide moderate and clinically significant treatment effects on a visual analogue scale (VAS) pain score (effect size: − 0.46; 95% CI − 0.82 to − 0.10; p = 0.01). The whole GSM extract improved gastrointestinal symptoms in OA patients taking anti-inflammatory medications. The GSM extract was considered to be generally well tolerated in most of the studies. Conclusion The overall analysis showed that GSM provided moderate and clinically meaningful treatment effects on OA pain. However, the current evidence is limited by the number and quality of studies, and further larger and high-quality studies are needed to confirm the effectiveness and to identify the optimal GSM format. Nevertheless, it is worth considering using GSM extracts especially for patients seeking alternative pain relief treatments with fewer side effects compared to conventional treatment.

Dietary agrobiodiversity for improved nutrition and health outcomes within a transitioning indigenous Solomon Island food system - Chris Vogliano; Jessica E. Raneri; Jane Coad; Shane Tutua; Carol Wham; Carl Lachat; Barbara Burlingame (Food Security, 2021)
Indigenous food systems of Pacific Small Island Developing Countries contain vast biological and cultural diversity. However, a nutrition transition is underway, characterized by shifts away from traditional diets in favour of imported and modern foods, contributing to some of the highest rates of obesity and Diabetes Type 2 Mellitus in the world. Using a mixed method approach, this study aimed to assess dietary agrobiodiversity’s relationship with nutrition indicators related to diet quality and anthropometrics within the context of the rural and Indigenous food system of Baniata village, located in the Western Province of Solomon Islands (Melanesia). A secondary aim was to evaluate the contribution of agrobiodiversity from the local food system to diet quality. A comprehensive nutrition survey was administered to the women primarily responsible for cooking of randomly selected households ( n = 30). Additionally, 14 participatory focus group discussions captured the historical narrative of food system transitions, were hosted over a period of seven days, and included men, women and youth. Dietary intakes of the participants were reported below the estimated average requirement (EAR) for several essential nutrients, including protein (53%), calcium (96.6%), vitamin B1 (86.6%), vitamin B2 (80%), vitamin A (80%), zinc (40%) and fibre (77%). Focus group participants built a timeline of key historical and climatic transitions perceived to be drivers of dietary shifts away from traditional foods and towards imported and processed foods. Participants identified 221 species and varieties of agrobiodiverse foods available for cultivation or wild collection. Based on 24 h diet recalls, 87 were found to be utilised. Participants who consumed foods of a wider diversity of species richness had a higher probability of achieving recommended nutrition intakes and a lower body fat percentage (r 2 = 0.205; p = 0.012). Our results suggest a nutrition transition is underway, and strategies harnessing traditional knowledge of nutrient-dense, agrobiodiverse foods can help improve food and nutrition security.

Use of Iodine Supplements by Breastfeeding Mothers Is Associated with Better Maternal and Infant Iodine Status - Ying Jin; Jane Coad; Shao J Zhou; Sheila Skeaff; Cheryl Benn; Louise Brough (Biological Trace Element Research, 2021)

Parents’ experiences of caring for a young person with neurofibromatosis type 1 (NF1): a qualitative study - Jenny Barke; Jane Coad; Diana Harcourt (Journal of Community Genetics, 2016)